To the revision of the genus Thionia Stål (Hemiptera, Fulgoroidea, Issidae), with description of new genera and new subtribe - Gnezdilov, Vladimir M. (Zootaxa, 2018)
New subtribe, Oronoquina subtrib. n., is erected for the genus Oronoqua Fennah, 1947 in the tribe Thioniini Melichar. New genera, Fowlerium gen. n. (type species: Thionia naso Fowler, 1905) and Aplos gen. n. (type species: Issus simplex Germar, 1830) are erected in the subtribe Thioniina Melichar. Thionia acuta Doering, 1941 and T. producta Van Duzee, 1908 are transferred to Fowlerium gen. n. The photos of type specimen of Issus cinctifrons Stål, 1854 are examined and compared with original description of Issus rubrocostatus Spinola, 1839 (currently Thionia rubrocostata (Spinola, 1839)). I. cinctifrons is reinstalled from synonymy with I. rubrocostatus as Thionia cinctifrons (Stål, 1854). Diagnosis of Thionia sensu stricto is given basing on the characters of T. cinctifrons. Generic status of Cheiloceps Uhler, 1895 is discussed and confirmed. Thionia argo Fennah, 1949, T. anguillana Fennah, 1965, T. borinqueta Caldwell et Martorell, 1951, and T. puertoricensis Caldwell et Martorell, 1951 are transferred to the genus Cheiloceps Uhler. Hind wing venation characters of Issidae are discussed.